Bone marrow mesenchymal stem cell-derived exosomes promote tendon regeneration by facilitating the proliferation and migration of endogenous tendon stem/progenitor cells. (1st April 2020) - Yu, Huilei; Cheng, Jin; Shi, Weili; Ren, Bo; Zhao, Fengyuan; Shi, Yuanyuan; Yang, Peng; Duan, Xiaoning; Zhang, Jiying; Fu, Xin; Hu, Xiaoqing; Ao, Yingfang
Abstract: Mesenchymal stem cells (MSCs)-derived exosomes are being increasingly focused as the new biological pro-regenerative therapeutic agents for various types of tissue injury. Here, we explored the potential of a novel exosome-based therapeutic application combined with a local fibrin delivery strategy for tendon repair. After discovering that bone marrow mesenchymal stem cells-derived exosomes (BMSCs-exos) promoted the proliferation, migration and tenogenic differentiation of tendon stem/progenitor cells (TSPCs) in vitro, we embedded BMSCs-exos in fibrin and injected it into the defect area of rat patellar tendon, and the results showed that the exosomes could be controlled-released from the fibrin, retained within the defect area, and internalized by TSPCs. BMSCs-exos embedded in fibrin significantly improved the histological scores, enhanced the expression of mohawk, tenomodulin, and type I collagen, as well as the mechanical properties of neotendon, and also promoted the proliferation of local TSPCs in vivo. Overall, we demonstrated the beneficial role of BMSCs-exos in tendon regeneration, and that fibrin-exosomes delivery system represents a successful local treatment strategy of exosomes. This study brings prospects in the potential application of exosomes in novel therapies for tendon injury. Statement of Significance: Mesenchymal stem cells have been identified as a preferred approach in tissue regeneration. In this study, we reported bone marrow mesenchymal stem cells (BMSCs) promote the proliferation and migration of tendon stem/progenitor cells (TSPCs) via the paracrine signaling effect of the nanoscale exosomes. We also demonstrated that the application of BMSCs-derived exosomes might be a promising approach to activate the regenerative potential of endogenous TSPCs in tendon injured region, and fibrin-exosomes delivery system represents a successful local treatment strategy of exosomes. Graphical abstract: Image, graphical abstract